Pemanfaatan Modalitas Politik Rezki Mulfiati Lutfi dalam Menghadapi Pemilu 2024 - Mulawarman, Mulawarman; Naharuddin, Andi; Banggu, Masni; Hidayatullah, Fauzan; Tusriadi, Tusriadi (Universitas Muhammadiyah Sorong, 2023)
This research aims to find out what steps female politicians must take to utilize political modalities to gain public sympathy. The research method used is qualitative research with a descriptive analysis approach. Data obtained through primary and secondary data. The research results show that the modalities at hand can influence voters' attitudes and can change people's views through the influence of an actor and a political party. Utilizing family networks is the right step to gain political support by gathering a mass base, especially in political outreach activities and political campaigns. Likewise, the political capital he has as the holder of the most votes in the National Democratic Party (Nasedem) already has loyal sympathizers and strengthens his strength to retain voters' votes, and economic capital as a supporting factor in campaign activities, especially financing campaign props, such as print media. and electronic media.